The efficacy of training insertion skill on a physical model colonoscopy simulator - Plooy, Annaliese M.; Hill, Andrew; Horswill, Mark S.; Cresp, Alanna St.G.; Karamatic, Rozemary; Riek, Stephan; Wallis, Guy M.; Burgess-Limerick, Robin; Hewett, David G.; Watson, Marcus O. (Endoscopy International Open, 2016)
Background and study aims: Prior research supports the validity of performance measures derived from the use of a physical model colonoscopy simulator – the Kyoto Kagaku Colonoscope Training Model (Kyoto Kagaku Co. Ltd., Kyoto, Japan) – for assessing insertion skill. However, its use as a training tool has received little research attention. We assessed the efficacy of a brief structured program to develop basic colonoscope insertion skill through unsupervised practice on the model. Participants and methods: This was a training study with pretesting and post-testing. Thirty-two colonoscopy novices completed an 11-hour training regime in which they practiced cases on the model in a colonoscopy simulation research laboratory. They also attempted a series of test cases before and after training. For each outcome measure (completion rates, time to cecum and peak force applied to the model), we compared trainees’ post-test performance with the untrained novices and experienced colonoscopists from a previously-reported validation study. Results: Compared with untrained novices, trained novices had higher completion rates and shorter times to cecum overall (Ps < .001), but were out-performed by the experienced colono-scopists on these metrics (Ps < .001). Nevertheless, their performance was generally closer to that of the experienced group. Overall, trained novices did not differ from either experience-level comparison group in the peak forces they applied (P > .05). We also present the results broken down by case. Conclusions: The program can be used to teach trainees basic insertion skill in a more or less self-directed way. Individuals who have completed the program (or similar training on the model) are better prepared to progress to supervised live cases.